(untitled) (Cambridge, Mass, 1990)
This study analyzes the nature of prewar Japanese entrepreneurship, the links between technology and investment, the emergence of a class of scientific managers, and the relationship of business strategy to imperialism in the years leading up to World War II.
Keywords: Công nghiệp hoá chất,Chemical industry; Lịch sử,History; Thế kỷ 20,20th century; Nhật Bản,Japan